Analysis of Coal Swelling Deformation Caused by Carbon Dioxide Adsorption Based on X-Ray Computed Tomography. (16th September 2018) - Nie, Xiangrong; Chen, Junbin; Cao, Yi; Gong, Diguang; Deng, Hao
Abstract : The geologic sequestration of carbon dioxide by coal beds leads to the swelling deformation of coal. In order to investigate the swelling deformation characteristics at the microscopic scale, X-ray computed tomography (CT) scanning technology was used. X-ray CT scanning technology detects the internal structure, deformation, and porosity of coal at different gas pressures. Results show that swelling deformation is nonuniform, which is caused by the heterogeneity of the coal structure. Through quantitative measurement of the distance between fractures and pseudocolor processing of CT images, we observed that fractures gradually close with the increase of adsorption pressure. As adsorption pressure increases, the porosity of coal decreases, and the density of coal increases.